The monk who sold his Ferrari a spiritual fable about fulfilling your dreams and reaching your destiny - Sharma, Robin S (London Thorsons, 2015)
Wisdom to Create a Life of Passion, Purpose, and Peace
Keywords: Self-realization--Fiction.